A knowledge and analytical-based intelligent system for customising logistics management. (2nd January 2007) - Chow, Harry K.H.; Choy, K.L.; Lee, W.B.; Lam, T.C.
In recent years, logistics service companies have been seeking numerous technologies and logistics information systems to support daily logistics operations. However, the planning and decision making of logistics activities is still done manually, where subjective judgment is made by Logistics Service Providers (LSP) through analysing multiple knowledge/information sources and various quantitative and qualitative criteria. In this paper, the use of an intelligent Decision Support System (DSS), namely, Knowledge and Analytical-based Intelligent System (KAIS), to embed the information communication and decision support technology in aiding such decision-making process is explained. KAIS is developed by integrating Analytic Hierarchy Process (AHP), Case-Based Reasoning (CBR) and portal technologies seamlessly, which is suitable for application in various dynamic logistics operations environment. By using KAIS in Eastern Logistics Limited (ELL), the overall logistics service quality and customer satisfaction level is significantly enhanced through making accurate decision and systematic planning of logistics operations.